The Contribution of Tourism Objects in Banyumas Kota Lama to the Hotel Occupancy - Deliana, Dian (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This study aims to assess the impact of tourism attractions in the Kota Lama Banyumas area on hotel occupancy rates. This study employed a qualitative research methodology utilizing a descriptive approach. Qualitative research methods are employed to assess the state of tourism in the Banyumas Kota Lama area. This area lacks optimal and professional management of tourist attractions, leading to suboptimal economic benefits for the local community and low hotel occupancy rates in the vicinity of these destinations. The study findings indicate that the presence of tourist attractions in the Banyumas Kota Lama tourist destination has a significant impact on the local community's economy through increased hotel occupancy. The rise in tourist visits to Banyumas Kota Lama has led to an expansion of employment opportunities in the tourism sector. The hotel industry in the region will see a rise in occupancy due to the growing number of tourists. Hoteliers will directly benefit from the rise in visitor numbers, leading to an increase in their revenues. This can incentivize hoteliers to enhance their hospitality infrastructure and provide superior services in order to attract a larger number of tourists. Moreover, the growing tourist influx will positively affect Micro, Small, and Medium Enterprises (MSMEs) in the vicinity.